Building Privacy into Software Products and Services. - Knutson, T.R.
In the marketplace, customer trust is paramount. As consumers increasingly rely on the Internet for shopping, banking, and other daily activities, privacy is both a major public concern and a barrier to e-commerce growth: fear of data breaches and identity theft threaten to erode trust in the Internet. Once the core privacy team (CPT) is built, it can begin to define the program, deploy its processes, and enforce the rules.